Description of Posyandu Implementation During the Covid-19 Pandemic in Tegal Rejo Village, Medan Perjuangan District - Zahratul Idami; Annisa Rahmah Nasution; Dhieva Zahwa Gunawan; Fitri Anisah Nasution; Nuranisa Karina Berutu (LPPM UIKA Bogor, 2022)
The high number of Covid-19 cases in Medan city also had an impact on the delay in Integrated Healthcare Center (IHC) activities, routined monthly activities, that are managed and organized from, by, for, and with the community in the implementation of health development. The purpose of this study was to describe the implementation of IHC during the pandemic in Tegal Rejo Village of Medan Perjuangan Subdistrict in 2021. This study used a qualitative approach with descriptive analysis methods. Key informants in this study were 3 Cadres of IHC and triangulation informants used for validity were 2 Village Midwives in the local sub-district. The result of this research is that Cadres of IHC already know what their duties are and have done socialization, but only to mothers and the elderly who come to the integrated healthcare center. The conclusion is that there is no change in the IHC schedule during the Covid-19 pandemic, socialization is given to mothers and the elderly who come to the IHC, but it has not been given to the general public. Facilities and implementation of IHC during the pandemic are by health protocols such as washing hands, and using masks and hand sanitizers for integrated healthcare center employees.